Actor Network Composition in Stunting Prevention in Polewali Mandar Regency - Zulfiani, ‎; Susanti, Gita; Rusdi, Muhammad (KnE Social Sciences, 2025)
According to Presidential Regulation Number 72 of 2021 about the Acceleration of Stunting Reduction, which is multisectoral, efforts are being made to lower the stunting rates in Polewali Mandar Regency by involving all relevant processes and actors. Network discussion will decide the parties, organizations, and actors. ,are . The combination of actors can be interpreted as a network population where they have certain goals and have their respective roles in the network. The network actor composition approach is used to assess the diversity and influence of the number of actors in the network as a major part of the actor composition in network effectiveness. The methods used to compile this research are interviews and surveys of academic literature in the field of public administration relevant to network composition. In addition, efforts were also made to search through various sources, both from official government documents and various news in the mass media, both print and electronic, to describe practices related to network composition. The results show that the stunting prevention program is multisectoral, involving not only government agencies but also nongovernment agencies, mass media, communities, the private sector, and academics. In addition, the diversity of actors involved allows actors to exchange resources as a consequence of their limited resources.